An analysis of droughts in Maharashtra by a modified Palmer's approach - SAMBASIVARAO, A; SUBRAMANIAM, AR (MAUSAM, 1986)
Droughts pose a serious problem in rainfed agriculture of Maharashtra. The commencement and cessation of different intensities of meteorological droughts during 1934- 77 at 23 locations of the State are identified by using the Palmer's approach. While adopting Palmer's approach, the definition of potential runoff and the weighting factors originally given by him are suitably modified for the climatic conditions of Maharashtra. The modified drought indices performed well for identification of various classes of droughts in the region. The analysis shows that the spatial distribution of drought prone areas during kharif (June-September) is similar to that of rabi season (October-February) in the region. During kharif season alone severe/extreme drought conditions prevailed for 28 out of 44 years in the State. But there are few stations like Kolhapur and Sironcha (Sub-humid) where the drought situation never touched the extreme conditions.